Posttraumatic Bilateral Basal Ganglia Bleed: A Report of Three Extremely Rare Cases - Reddy, Musali Siddartha; Beniwal, Hemant; Karla, Ravi; Gollapudi, Prakash Rao (Indian Journal of Neurosurgery, 2019)
Basal ganglia bleed, though common in hypertensive, is unusual in posttraumatic patients. Bilateral basal ganglia hematoma following trauma is extremely rare and is limited to few case reports. The authors report three cases of bilateral basal ganglia hematomas in traumatic patients. All the cases were managed conservatively.
Keywords: bilateral; basal ganglia; hematoma; traumatic